Solid Waste Management System in Tanjungpura University: 3Rs concept integrated with the Waste Bank - Arifin Ghandi; Dwi Susilowati; Hendri Sutrisno (Universitas Diponegoro, 2023)
Tanjungpura University is one of the State Universities in West Kalimantan. Waste management in the Tanjungpura University area still applies the old waste management paradigm. Waste management in the Tanjungpura University area still applies the old paradigm of waste management, which has an impact on environmental problems, because waste management has not been handled optimally. Therefore, it is necessary to plan a waste management system with a new paradigm that integrates the 3R concept (Reuse, Reduce and recycle) with the Waste Bank. The research data were obtained through in-depth interviews and field sampling using the SNI-19-3964-1994 method for 8 days. The results of the study show that waste generation in 2035 will be 39,035 l/day. The projected results of waste generation and waste composition form the basis for waste management system planning. The waste management system includes sorting waste at the source, designing segregated containers, designing waste collection cars, processing organic and inorganic waste, and designing 3R-based Waste Processing Site which is integrated with the Waste Bank. This plan is expected to help develop Tanjungpura University with a Green Campus concept.